Photoinitiated long-lived charge separation with near-unity quantum yield in donor-acceptor1-acceptor2 systems for artificial photosynthesis. Issue 33 (17th August 2017) - Han, Won-Sik; Veldkamp, Brad S.; Dyar, Scott M.; Eaton, Samuel W.; Wasielewski, Michael R.
Abstract: We report the synthesis and photophysical characterization of isomeric donor-acceptor1 -acceptor2 (D -A 1 -A 2 ) triads each comprising a perylene donor (D ) connected by a xylene bridge to a naphthalene-1, 8-dicarboximide primary acceptor (NMI, A 1 ) that is, in turn, covalently linked to a naphthalene-1, 4:5, 8-bis(dicarboximide) secondary acceptor (NDI, A 2 ) through a benzene ring at its ortho, meta or para positions (Per-Xy-NMI- x -NDI ). Selective photoexcitation ofPer produces bothPer + andNDI ‒ simultaneously with time constants of ∼50 ps in benzonitrile and ∼80 ps in toluene with a >98% yield. This is much faster than expected for single-step electron transfer from 1* Per toNDI and is consistent with a two-step mechanism, 1* Per-Xy-NMI- x -NDI →Per + -Xy-NMI ‒ - x -NDI →Per + -Xy-NMI- x -NDI ‒, in which the second step is much faster than the first step. In addition, preserving long-lived charge separation in these systems is found to depend on inhibiting charge recombination by a triplet radical ion pair recombination pathway. Graphical abstract: